Genetic Characterization of Fungi Isolated from the Environmental Swabs collected from a Compounding Center Known to Cause Multistate Meningitis Outbreak in United States Using ITS Sequencing - Irshad M. Sulaiman; Emily Jacobs; Steven Simpson; Khalil Kerdahi (Pathogens, 2014)
A multistate fungal meningitis outbreak started in September of 2012 which spread in 20 states of the United States. The outbreak has been fatal so far, and has affected 751 individuals with 64 deaths among those who received contaminated spinal injections manufactured by a Compounding Center located in Massachusetts. In a preliminary study, Food and Drug Administration (FDA) investigated the outbreak in collaboration with Centers for Disease Control and Prevention (CDC), state and local health departments, and identified four fungal and several bacterial contaminations in the recalled unopened injection vials. This follow-up study was carried out to assess DNA sequencing of the ITS1 region of rRNA gene for rapid identification of fungal pathogens during public health outbreak investigations. A total of 26 environmental swabs were collected from several locations at the manufacturing premises of the Compounding Center known to have caused the outbreak. The swab samples were initially examined by conventional microbiologic protocols and a wide range of fungal species were recovered. Species-identification of these microorganisms was accomplished by nucleotide sequencing of ITS1 region of rRNA gene. Analysis of data confirmed 14 additional fungal species in the swabs analyzed.